AN ANALYSIS OF EDUCATIONAL VALUE IN BILAL MOVIE: A NEW BREED OF HERO - Andika Wahyu Pratama; Dewi Nurmala (PHILOLOGY Journal of English Language and Literature, 2021)
The objectives of the research were to find the educational value and benefits of watching movie. The source of the movie discussed in this research is Bilal: A New Breed of Hero. There were two sources of data used in this thesis. The main data source was obtained from the movie in the form of dialogue scripts between characters in the movie. The second data was obtained from articles related to research and other sources from the internet. The type of research in this movie was descriptive qualitative. It was used to answer the questions in problem of the research and was presented in the form of a description. Based on the analysis, it was known that there were several educational values found, including: honest, brave, peace, confident and potential, discipline, loyal and trustworthiness, respect, loving and affection, kind and friendly, fair and humanist. In addition, there were two benefits of watching Bilal: A New Breed of Hero Movie, namely: as medium of education and medium of entertainment.